Dynamic Capabilities of ICT Company in the Smart City Field - Abdelgawad, Hossam Mohamed Kamel (Digital Repository of Theses, 2025)
The dynamic capabilities of Information and Communication Technology (ICT) companies play a pivotal role in the development of smart cities. This research investigates how ICT firms can effectively sense, seize, and transform in response to the volatile, uncertain, complex, and ambiguous (VUCA) environment of smart city initiatives. The study develops a comprehensive framework for measuring these dynamic capabilities and applies analytical models, including the Analytic Hierarchy Process (AHP) and Exploratory Factor Analysis (EFA), to evaluate decision-making processes. By integrating concepts from dynamic capability theory and smart city frameworks, this research provides a novel approach to assessing the strategic adaptability of ICT companies. The findings highlight the importance of critical success factors (CSFs) in fostering innovation and sustaining competitive advantages for ICT firms engaged in smart city projects. Key insights emphasize the significance of collaborative decision-making, platform integration, and the adoption of disruptive technologies. This study offers practical recommendations for ICT companies and policymakers, advocating for a balanced approach to technological innovation, resource allocation, and stakeholder engagement. The research contributes to academic discourse by bridging the gap between dynamic capability theory and smart city development, providing a foundation for future empirical and theoretical advancements.